Logistics risk management in the supply chain in a pharmaceutical distribution organization - Neves, Hellen Leite; Silva, Yuri Laio Teixeira Veras (Brazilian Journal of Production Engineering, 2025)
In the contemporary scenario, one of the main challenges faced by companies concerns the need to manage the flow of products and services that make up the supply chain, with the purpose of identifying how the integration of links and the sharing of information among them occurs. In this context, supply chain management becomes essential for studying the flow of materials, information, and products among the various members that constitute it. Given this scenario, the objective of this study is to model the supply chain of a pharmaceutical company that distributes products in the hinterlands of Paraíba, Brazil. To this end, the initial configuration of the organization’s supply chain was established, and mapping strategies were applied, taking into account the location, lead time, relationships, and quantity of product families supplied by the components of the supply chain. Finally, the data obtained through the mapping process were analyzed. As a result, it was possible to observe, at each level of the chain, how many suppliers and customers the company has in each region of the country, the number of product families each supplier delivers, the nature of relationships among the various links in the chain, and which suppliers have longer lead times and how many have shorter ones.